The Effect of Endotoxin on General and Coronary Haemodynamics and Metabolism, and its Relation in Certain Infectious Diseases - G.M. Maxwell (Paediatrica Indonesiana, 1975)
Shock occurs in gram-negative septicaemia, dengue, and other infections: to understand the situation better, a study was made of the effects of endotoxin on the general and coronary circulation of intact animals. Cardiac output (Fick), coronary flow (N2O Fick), vascular pressures, glucose lactate, pyruvate, non-esterified fatty acid (NEFA), and C14 palmitate levels, were measured before and after the injection of Serratia marcescens endotoxin into healthy anaesthetized dogs.Cardiac output, vascular pressures, and cardiac work fell precipitously. Coronary blood flow, myocardial O2 consumption, and cardiac efficiency decreased by 50%.Whole-body glucose, lactate, pyruvate, and NEFA increased, but no change occurred in the myocardial extraction of these substances. The myocardial oxidation of C14 palmitate increased.The general haemodynamic changes are similar to those occurring in patients; it is suggested that the changes in the coronary circulation seen in animals may also occur in the clinical situation. Other animal studies with a histamine releaser (Tween 20), gave results similar to those of endotoxin. Anaphylotoxins may then also be relevant to the "shock" state of certain infections.